Annual report of the committee on gynecologic oncology, the Japan Society of Obstetrics and Gynecology: Annual patient report for 2019 and annual treatment report for 2014. Issue 7 (27th May 2022) - Yoshino, Kiyoshi; Kurita, Tomoko; Takahashi, Fumiaki; Nagase, Satoru; ,
Abstract: Aim: To provide information including the trend of gynecological malignancies in Japan, we hereby present the Annual Patient Report for 2019 and the Annual Treatment Report for 2014, on the outcomes of patients who started treatment in 2014. Methods: The Japan Society of Obstetrics and Gynecology maintains an annual tumor registry, where information on gynecological malignancies from various participating institutions is gathered. The data of patients whose treatment with gynecologic malignancies was initiated in 2019 were analyzed retrospectively. Survival of the patients who started treatment with cervical, endometrial, and ovarian cancer in 2014 was analyzed by using the Kaplan–Meier, log‐rank, and Wilcoxson tests. Results: Treatment was initiated in 2019 for 7983 patients with cervical cancer, 12 631 with endometrial cancer, 7737 with ovarian, tubal, and peritoneal cancer, 2222 with ovarian borderline tumors, and with the others (251 vulvar cancer, 148 vaginal cancer, 476 uterine sarcoma, 43 uterine adenosarcoma, 175 trophoblastic diseases). This clinicopathological information was summarized as the Patient Annual Report. The 5‐year survival rates of the patients with cervical cancer were 92.5%, 76.8%, 58.6%, and 29.5% for stages I, II, III, and IV, respectively. The 5‐year survival rates for the patients with endometrial cancer were 94.5%, 87.3%, 70.2%, and 26.5% for stages I, II, III, and IV, respectively. The 5‐year survival rates for the patients with ovarian cancer (surface epithelial‐stromal tumors) were 90.72%, 80.4%, 53.4%, and 31.6% for stages I, II, III, and IV, respectively. Conclusion: The annual tumor report is an important survey that provides knowledge on gynecological malignancy trends in Japan.